2022
DOI: 10.1038/s41587-022-01381-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a live attenuated influenza A vaccine by proteolysis targeting

Abstract: Live attenuated virus vaccines have been generated by several strategies, including cold-adapted live attenuated influenza vaccines (CAIVs), codon-deoptimized virus, premature termination codon-harboring virus, hyper-interferon-sensitive virus and viral-protein-altered virus 1-12 . However, current attenuation strategies are often accompanied by decrease or loss of safety, efficacy or productivity 1,[13][14][15][16] . In addition, immune escape due to rapid viral evolution poses a further challenge for traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Despite the use of existing vaccines, influenza still causes 3–5 million severe cases and .3–.65 million deaths worldwide each year, 1 highlighting the need for new vaccine strategies that can generate improved vaccines and thus expand our antiviral arsenal. In a proof‐of‐concept study, 2 Si et al. describe the development of a proteolysis‐targeting chimeric (PROTAC) vaccine technology by using the host cellular ubiquitin‐proteasome system to conditionally degrade influenza viral proteins (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Despite the use of existing vaccines, influenza still causes 3–5 million severe cases and .3–.65 million deaths worldwide each year, 1 highlighting the need for new vaccine strategies that can generate improved vaccines and thus expand our antiviral arsenal. In a proof‐of‐concept study, 2 Si et al. describe the development of a proteolysis‐targeting chimeric (PROTAC) vaccine technology by using the host cellular ubiquitin‐proteasome system to conditionally degrade influenza viral proteins (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
“… 4 Recent studies have demonstrated several strategies to design live attenuated vaccines that are in development. 2 , 4 , 5 , 6 , 7 Compared to these approaches, the PROTAC vaccine uses a distinct design principle—targeting viral protein to the host's ubiquitin‐proteasome system for degradation and thus attenuating viral replication.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations